A POLÍTICA PÚBLICA DE COMBATE AO TRABALHO EM CONDIÇÕES ANÁLOGAS À DE ESCRAVO: ARGUMENTOS ÉTICOS, MORAIS E PRAGMÁTICOS SOB UMA ÓTICA SISTÊMICA (Revista Paradigma, 2024)
The current research aims to understand public policies aimed at fighting working conditions analogous to slavery through an analysis of  the ethic, moral and pragmatic arguments regarding decent work and human rights. The study is justified both on scientific grounds, due to the relevance of developing academic work on the foundations of sound public policies to combat labour in conditions analogous to slavery as well as social ones, as it concerns human liberty and decent work. It aims to observe how public policies have assured the recognition of equality among people, the freedom of movement and decent working conditions. Its hypothesis is that, having human rights and solidarity as a premise, and by using ethical, moral and pragmatic arguments, it is possible to promote equality, liberty and decent work through public policies. This research used a deductive approach and the review of specialized literature. The results indicate the confirmation of the main hypothesis and, therefore, confirm the possibility of implementing sound public policies based on the promotion of equality, liberty and decent work, resulting in the improvement of workers' living conditions.
Keywords: Public policy. Slave work. Working conditions analogous to slavery. Ethical, moral and pragmatic arguments.